2009
DOI: 10.1111/igc.0b013e31819d82c3
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival After Fertility-Sparing Surgery for Epithelial Ovarian Cancer

Abstract: Fertility-sparing surgery is a reasonable alternative treatment for young women with stage I epithelial ovarian cancer desiring fertility preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 24 publications
2
47
0
1
Order By: Relevance
“…[112][113][114] For a young patient who wishes to maintain fertility, a unilateral salpingooophorectomy (USO; preserving the uterus and contralateral ovary) may be adequate for select unilateral stage I tumors (stage 1A and 1C, but not stage 1B) and/or low-risk ovarian tumors (ie, early-stage, grade 1 tumors; borderline tumors; see LCOH-6, LCOH-9, LCOH-10; pages 1141, 1143, and 1144, respectively). [115][116][117][118][119][120] Comprehensive staging may not be necessary for select patients, such as those with borderline epithelial tumors (see LCOH-6, page 1141).…”
Section: Primary Treatmentmentioning
confidence: 99%
“…[112][113][114] For a young patient who wishes to maintain fertility, a unilateral salpingooophorectomy (USO; preserving the uterus and contralateral ovary) may be adequate for select unilateral stage I tumors (stage 1A and 1C, but not stage 1B) and/or low-risk ovarian tumors (ie, early-stage, grade 1 tumors; borderline tumors; see LCOH-6, LCOH-9, LCOH-10; pages 1141, 1143, and 1144, respectively). [115][116][117][118][119][120] Comprehensive staging may not be necessary for select patients, such as those with borderline epithelial tumors (see LCOH-6, page 1141).…”
Section: Primary Treatmentmentioning
confidence: 99%
“…In most studies, including this review, fertility-sparing surgery has been defined as the preservation of ovarian tissue in one or both adnexa and the uterus in women of reproductive age [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39] (table 1). To date, 918 patients with EOC who underwent fertility-sparing surgery have been captured in the literature.…”
Section: Text Of Reviewmentioning
confidence: 99%
“…The safety of fertility-sparing surgery in women with stage IC and grade 3 EOC has not been determined, although the results of several recent series have suggested that fertility-sparing surgery is safe in patients with stage IC grade 1-2 EOC, regardless of the type of stage 1C (positive peritoneal cytology, capsule invasion or tumor rupture) [19,20,23,25,28,29,32,33,34,35,36,37,38,39]. Patients with preoperative or intraoperative tumor rupture, surface excrescences, or malignant cells in ascitic fluid or peritoneal washings are classified as having stage IC disease.…”
Section: Text Of Reviewmentioning
confidence: 99%
“…Because of the nonspecific symptoms and the lack of early diagnostic methods, EOC is extremely difficult to diagnose at an early stage. Nearly 70% of patients are diagnosed at an advanced stage (FIGOⅡ-Ⅳ), with a survival rate of 30-40% (Cannistra et al, 1993;Barnholtz-Sloan et al, 2003;Qiu H et al, 2011); however, if diagnosed at a localized stage (FIGOⅠ), the 5-year survical rate is 93% (Schlaerth et al, 2009). Therefore, a study on the molecular mechanism underlying ovarian cancer progression, including a search for a related target gene, is important for early diagnosis and effective therapy for ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%